Mechanism Analysis of the Effect of Cordycepin on Colorectal Cancer via Network Pharmacology and Experiment - Chen, Ya; Wang, Peng; Zhang, Mingzhu; Yang, Hao; Liang, Beibei (Combinatorial Chemistry & High Throughput Screening, 2025)
<span class=
Keywords: network pharmacology